IDENTIFIKASI JENIS ANGGREK EPIFIT (Orchidaceae) DI KAWASAN ARBORETUM SYLVA UNIVERSITAS TANJUNGPURA PONTIANAK - Purwanti, Purwanti; Manurung, Togar Fernando; Kartikawati, Siti Masitoh (JURNAL HUTAN LESTARI, 2021)
Arboretum Sylva UNTAN is an ex-situ germplasm conservation area, which has a variety of trees and undergrowth plants including epiphytes. Epiphytic orchids are orchids that grow riding on other plants, but do not harm the host plant. It is important to know the type of epiphytes that hitchhike on host plant can help management in the conservation of the area. For this reason, Epiphytic orchids and their host plant need to be done. This study uses a survey method, with census data collection techniques. Based on the results of the study, 49 types of epiphytic orchids were found as epiphytic orchids belonging to 23 genera and 36 host plant species. Epiphytic orchids that oppose the genus Bulbophyllum and Dendrobium. The dominance of the highest tree species in Acacia sp and A. pavonina. It has nothing to do with epiphytes with host plant species, but epiphytic orchids mostly found on the cantilever plant that has thicker bark, groove bark, stringy bark and a tough bark. Abiotic conditions The environment can distinguish species in the block area.Keywords: Epiphytes orchids, identification, Arboretum Sylva UNTAN.